The exhumation of the Northern Patagonian Massif Gondwana Planation surface due to uprising during the Oligocene - Aragón, Eugenio (2014)
The altiplano (or high plain) of the Northern Patagonian Massif is a large, 100,000 km2 geomorphological unit that rose from sea level to at least 1,200 metres above sea level (m a.s.l.) in Early Oligocene times, as a consequence of epeirogenic uplift. This uniform tableland feature is essentially a Cretaceous planation surface carved on Paleozoic igneous and metamorphic rocks of the Northern Patagonian Massif. This planation surface had been preserved by a thin and scattered cover of Maastrichtian-Danian marine sediments and Late Oligocene-Early Miocene basaltic flows. Erosion since Middle Miocene times at this tableland has exposed much of the Gondwana planation surface and developed numerous basaltic plateaus by relief inversion.